Maternal health situation in Empowered Action Group of states of India: A comparative analysis of state reports from National Family Health Survey (NFHS)-3 and 4 - Roy, Shreyasi; Sen, Jaydip (Anthropological Review, 2020)
Motherhood is often claimed as the most positive and fulfilling experience. Nevertheless, there exist several women whose motherhood was associated with suffering, ill-health and even death. The condition is graver in few states of India which are socioeconomically backward (also called Empowered Action Group of states). The present study adopted a narrative description of various key indicators of maternal health as outlined in the NFHS-3 and NFHS-4 state reports. The prime focus was to examine whether the performance of those states has got better or worse in these two survey reports. The study has also discussed various factors related to the performance of each key indicator of maternal health. The overall limiting success of maternal health status in these states calls for improvement in execution of various maternal health related activities.